Money Answers all things’: Wealth as Means of Belonging in Onuzo’s Welcome to Lagos - Mehellou Zohra (University Of Eloued جامعة الوادي, 2024)
Lagos has been an important setting for numerous Nigerian novels from Achebe, Ekwensi, Adichie, to Sefi Atta. The centrality of the city in these texts reflects its importance in the Nigerian context where it represents a modern lifestyle that attracts people to its glamour. Lagos, however, is a space of contradictions; of promise and chaos, of opportunity and struggle. Chibundu Unuzo’s novel Welcome to Lagos (2017) portrays the city as an escape and haven for the five characters who are running away from economic, military, and domestic violence. Once in the city, ethnic and linguistic differences melt away revealing a new structure of identification, that of money and wealth. In Lagos, wealth is the main border that divides the city and decides the social status of its inhabitants. Therefore, fitting and surviving in this space for the characters means securing a source of money. In this discussion, I reflect on how the need to access money by the five characters turns Lagos from a safe space to a threat. Moreover, I analyse how accessing the space of the city results in the characters redefining their differences and their sense of belonging. الملخص كانت لاغوس مكانًا مهمًا للعديد من الروايات النيجيرية، بدءًا من أتشيبي وإيكوينسي وأديتشي وحتى سيفي أتا. وتعكس مركزية المدينة في هذه النصوص أهميتها في السياق النيجيري حيث تمثل نمط حياة عصري يجذب الناس إلى سحرها. لكن لاغوس هي مساحة من التناقضات؛ من الوعد والفوضى، من الفرص والنضال. تصور رواية شيبوندو أونوزو "مرحبًا بكم في لاغوس" (2017) المدينة على أنها ملاذ وملجئ للشخصيات الخمس التي تهرب من العنف الاقتصادي والعسكري والمنزلي. بمجرد وصولهم إلى المدينة، تتلاشى الاختلافات العرقية واللغوية لتكشف عن بنية جديدة للهوية، وهي بنية المال والثروة. في لاغوس، الثروة هي الحدود الرئيسية التي تقسم المدينة وتقرر الوضع الاجتماعي لسكانها. لذلك، فإن الملاءمة والبقاء في هذا الفضاء بالنسبة للشخصيات يعني تأمين مصدر للمال. في هذه التقديم، اناقش كيف أن الحاجة إلى الوصول إلى الأموال من خلال الشخصيات الخمس حولت مدينة لاغوس من مكان آمن إلى تهديد. علاوة على ذلك، أقوم بتحليل كيف يؤدي الوصول إلى المدينة إلى إعادة تعريف الشخصيات لاختلافاتها وشعورها بالانتماء.
Intervention
Keywords: : Lagos; Capitalism; Welcome to Lagos; City; Identity; لاغوس; الرأسمالية; مرحبا بكم في لاغوس; المدينة; الهوية